EFEKTIVITAS EDUKASI GIZI MENGGUNAKAN MEDIA FLASHCARD TERHADAP PENGETAHUAN, SIKAP, DAN PERILAKU MENGENAI JAJANAN SEHAT PADA ANAK SEKOLAH DASAR - Alfani Audita Noviana; Umi Mahmudah; Mamat Rahmat; Fred Agung Suprihartono (Jurusan Gizi Poltekkes Kemenkes Bandung, 2026)
Children at the elementary school level are at high risk of food poisoning. According to data from the Ministry of Health in 2023, there were 4,792 cases of poisoning in Indonesia. One of the causes is indiscriminate snacking. Lack of knowledge about healthy snacks affects children's attitudes and behavior. Education has a significant role in increasing insight so that children can be smarter in the selection of food they consume. The focus of this study is to analyze how effective nutrition education using flashcards is in influencing knowledge, attitudes and behaviors related to healthy snack choices among elementary school students. The research design used in this study was a quasi experiment with two-group pre and post-test control group design. The number of samples in this study were 23 intervention group respondents at SDN 139 Sukarasa and 23 control group respondents at SDN 196 Sukarasa obtained through purposive sampling. The results indicated that nutrition education had no effect on knowledge (p=0.947), attitude in choosing healthy snacks (p=0.910), and behavior in consuming healthy snacks (p=0.052). There was a difference in the improvement of knowledge and behavior (p=0.025) and (p=0.003), but no difference was found in the improvement of the attitude of choosing healthy snacks